The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.amepre.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Child-Directed TV Advertising and Preschoolers’ Intake of Advertised Cereals

Abstract: Introduction: Child-directed TV advertising is believed to influence children's diets, yet prospective studies in naturalistic settings are absent. This study examined if child-directed TV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…), media, and other environmental effects (food access and advertisements) (reviewed in Beckerman et al, 2017). Therefore, it is important to strengthen the implementation of the International Code of Marketing of Breast-milk Substitutes (World Health Organization, 2018) and introduce restrictions on marketing of unhealthy foods to children, covering all media, including digital, and to close any regulatory loopholes, as current evidence indicates that child-directed advertising has a major impact on children's diets (Tatlow-Golden et al, 2016;World Health Organization, 2016;Emond et al, 2019). Building combined and well-coordinated interventions encompassing all these target areas is essential in managing successful nutrition programs (reviewed in Beckerman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…), media, and other environmental effects (food access and advertisements) (reviewed in Beckerman et al, 2017). Therefore, it is important to strengthen the implementation of the International Code of Marketing of Breast-milk Substitutes (World Health Organization, 2018) and introduce restrictions on marketing of unhealthy foods to children, covering all media, including digital, and to close any regulatory loopholes, as current evidence indicates that child-directed advertising has a major impact on children's diets (Tatlow-Golden et al, 2016;World Health Organization, 2016;Emond et al, 2019). Building combined and well-coordinated interventions encompassing all these target areas is essential in managing successful nutrition programs (reviewed in Beckerman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Data were from a community-based, prospective cohort study of preschool-age children to identify factors associated with preschool children's dietary intake. 21 Participants were recruited March 2014 to October 2015 from community sites in two New Hampshire, US cities; Facebook and participant referrals were also used. Eligible children were aged 3 to 5 years with no health condition impacting food intake and who lived with the enrolled parent at least 3 days a week or alternate weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Data were from a community‐based, prospective cohort study of preschool‐age children to identify factors associated with preschool children's dietary intake . Participants were recruited March 2014 to October 2015 from community sites in two New Hampshire, US cities; Facebook and participant referrals were also used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2014 analysis of cold cereals sold in the United States found that 92% of cereals had added sugar, and that all cereals that were marketed to children contained added sugar. On average, children's cereals have 40% more sugar than cereals marketed to adults and may contain more sugar than cookies (22). Television advertising of high-sugar breakfast cereals that is directed at children has been positively associated with higher intake of high-sugar cereals (23).…”
Section: Discussionmentioning
confidence: 99%